Оценка финансовой безопасности предприятия на основе идентификации его финансового состояния - Смирнов, Ю.А.; Панфилова, Т.С. (Економіка промисловості, 2013)
Досліджено методичні підходи до оцінки фінансової безпеки підприємства, визначено їх переваги та недоліки. Розроблено алгоритм оцінки фінансової безпеки підприємств телекомунікаційної галузі за допомогою дискримінантного аналізу. Встановлено критерій ідентифікації стійкого чи нестійкого фінансового стану підприємства.
Ключові слова: фінансова безпека, фінансовий стан, телекомунікаційна галузь, константа дискримінації. Исследованы методические подходы оценки финансовой безопасности предприятия, определены их преимущества и недостатки. Разработан алгоритм оценки финансовой безопасности предприятий телекоммуникационной отрасли на основе дискриминантного анализа. Установлен критерий идентификации устойчивого или неустойчивого финансового состояния предприятия.
Ключевые слова: финансовая безопасность, финансовое состояние, телекоммуникационная отрасль, константа дискриминации. The current state of Ukrainian economy is characterized by significant fluctuations of internal and external factors in companies’ operation environment, serious threats to their financial position, and a high degree of financial risks. That is why one of the important goals of financial management is to promote the financial safety of the company.
Analysis of existing techniques for assessing the degree of company’s financial safety has identified a number of problems. The main ones are the lack of standard criteria, metrics and methodological approaches to determine the degree of company’s financial safety.
The goal of present research is to work out a technique for assessing the degree of company’s financial safety based on the key indicators of financial position. Constant monitoring of changes in company’s financial position is an important indicator of its financial safety. We recommend using following financial ratios for multipurpose assessment of financial position: equity ratio, accounts receivables to accounts payable ratio, asset coverage ratio, asset mobility ratio. It was developed a discriminant function for telecommunications industry companies. The degree of influence of key financial indicators on a discriminant functionwas determined. A criterion to identify stable or unstable status of company’s financial position was substantiated.
The suggested technique for assessing the degree of company’s financial safety can be used by the internal audit service or internal security service. Financial safety professionals (or financial safety analysts) have to monitor a company’s financial position in real time and quickly react to any changes. Furthermore, an information system has to be developed for comprehensive and objective monitoring aimed to detect and predict internal and external threats to the company’s financial safety. On the basis of the information received it must be developed a set of short-term and long-term measures to counteract the impact negative factors, as well as measures aimed to prevent and overcome the possible negative backwash of threats.
Keywords: financial security,financial condition, indicator, telecommunications industry, constant discrimination.